Need a Market Facing Institutional Leadership for Growth of FPOs - Natarajan, Ravishankar (Journal of Agricultural Extension Management, 2022)
High mortality and very few FPOs growing beyond the size of a small scale industry (SSI), even these are seen as an entrepreneurial success than of a farmer collective. Therefore, it is unrealistic that each of the few thousand FPOs in the country would be able to turn into business houses of some stature, with only capacity building and hand holding services by Cluster Based Business Organisations (CBBOs). Instead of every FPO going to market, the strategy proposed is to have FPOs access markets through Anchor Institutions (AI) that would be value chain specific, market-oriented and to be managed by a professional organisation. Under a Build-Operate-Train-Transfer (BOTT) model FPOs would be suppliers of quality produce, for 4 years, after the business is established, concurrently as the FPO directors are exposed to the organisation, the original promoters would transfer ownership to vendor FPOs of the state, more or less on equal basis. FPOs, just as a village milk society, would specialise in production and postharvest, while all commercial and market requirements are vested with the AI. Under the FPO policy for 10,000 FPOs by the GOI, the mandate of the CBBOs is to promote FPOs and support each of them to individually work on their business plan. The policy modification sought is to provide for the CBBOs to set up dedicated Sec 8 company as AIs to manage business strategy for specific value chains to be supported financially, under the BOTT model